PENGGABUNGAN GUGATAN GANTI KERUGIAN DALAM PERKARA PIDANA PENIPUAN DAN PENCUCIAN UANG TANPA MENEMPUH MEDIASI: Combination of Compensation Claim Cases in Fraud and Money Laundering Criminal Cases That Did Not Undergo Mediation - Nafrali Cahya Putri Prakoso; Muriani (Faculty of Law, Universitas Trisakti, 2024)
The existence of regulations regarding combining claims for compensation into criminal cases aims to provide opportunities for victims of criminal acts to obtain material compensation. Decision Number 1907/Pid.B/2021/PN.TNG is a decision in which the Tangerang District Court Panel of Judges granted a request to combine the claim for compensation into the criminal cases with reference to Article 98 and 99 of the Criminal Procedure Code. The formulation of the problem examined is whether the procedural process in examining the merger of claims for compensation in criminal cases carried out without mediation has followed the applicable rules. Normative research method has been used in this research that is followed by descriptive-analytic in nature, using primary and secondary data which is analyzed qualitatively, and conclusions are based on deductive reasoning. The research results show that mediation efforts were not carried out, nor did the Panel of Judges order the parties to undertake mediation efforts. The Conclusion is mediation efforts was not carried out first and the Panel of Judges did not order the parties to take mediation, this is a deviation from PERMA Number 1 Year 2016, so that this mergering cases does not follow the applicable law rules.